The precursors of second language acquisition : a cross-linguistic study. - Or, Hui Fang. (2013)
Cross-linguistic transfer in second language acquisition is an active area of research. Second language (L2) learners bring with them their first language (L1) experience; in the lexical dimension, experience with the L1 orthography influences L2 lexical processing. Using the data from sixteen English-Chinese biliterates, this study investigated cross-linguistic transfer arising from previous language experience with both alphabetic and logographic languages during the learning of artificial languages that were orthographically similar to English and Chinese. A battery of cognitive and literacy-related tasks was administered at pre-training. Two miniature artificial languages modeled after English and Chinese in terms of mapping principle were created and each language was learned over a span of three training sessions. Results show that the early bilinguals were sensitive to the probabilistic information specific to the respective artificial languages, thereby demonstrating associative learning. Correlation analyses further revealed that phonological awareness and visual sequential memory were associated with successful learning for the alphabetic artificial language whereas English orthographic skills and visual-spatial skills were associated with the logographic artificial language learning performance. The findings suggest that there may be precursors to learning a L2 but cognitive factors associated with cross-language transfer seems to be largely influenced by previous linguistic experience.